Lethal State : A History of the Death Penalty in North Carolina - Kotch, Seth (Book collections on Project MUSE., 2019)
For years, American states have tinkered with the machinery of death, seeking to align capital punishment with evolving social standards and public will. Against this backdrop, North Carolina had long stood out as a prolific executioner with harsh mandatory sentencing statutes. But as the state sought to remake its image as modern and business-progressive in the early twentieth century, the question of execution preoccupied lawmakers, reformers, and state boosters alike. In this book, Seth Kotch recounts the history of the death penalty in North Carolina from its colonial origins to the present. He tracks the attempts to reform and sanitize the administration of death in a state as dedicated to its image as it was to rigid racial hierarchies. Through this lens, Lethal State helps explain not only Americans' deep and growing uncertainty about the death penalty but also their commitment to it. Kotch argues that Jim Crow justice continued to reign in the guise of a modernizing, orderly state and offers essential insight into the relationship between race, violence, and power in North Carolina. The history of capital punishment in North Carolina, as in other states wrestling with similar issues, emerges as one of state-building through lethal punishment. --! From publisher's description.